The Real Project is Better than Conventional Paper Assignment; A View from the Student Perspective - Islami, Annisa Permata (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
There are several types of assignment given by teacher to the student. The purpose of the assignment is actually to increase the student understanding of certain topic. In this study, the powerful of a real project assessment has been examined in increasing the student understanding especially in the biology topic of SMA curriculum. A real project entitled âPertumbuhan Kecambahâ was assigned to the student starting from seeds selection, seeding to the polybag, and the growth observation for the total of two weeks. The collected data were processed, analyzed and finally presented into the compacted report. Selected student was then presenting the project. This research took the student of 12 IPA 5 - SMA 12 Pekanbaru as the population of the research. The interview method was used to obtain the opinion of the given project. A total of 21 students agree with the real project compared than conventional paper assignment. Whilst, 10 students strongly agree, 5 students disagree, and 2 students abstain. Mostly the student can easily answer why the seed grow vary toward the sun light intensity scientifically. This is an evident that the real project is better than conventional paper assignment.